Symptomatic uterine leiomyomatosis with intracaval and intracardiac invasion: Video case report - Débora Faciochi Cassol; Frederico José Ribeiro Teixeira Junior; Sérgio Dias do Couto Netto; Lenira Chierentin Rengel; Luciana Ragazzo; Fábio Antonio Gaiotto; Edivaldo Massazo Utiyama (Elsevier, 2023)
Background: Fibroid is the most prevalent benign tumor of the female genital tract. Intravenous and intracardiac leiomyomatosis (IVL and ICLM, respectively) are rare complications that present with symptoms of pulmonary thromboembolism and heart failure and whose etiology, despite controversial, is a direct vascular invasion by a primary uterine leiomyoma. Case presentation: We present the case of a 31-year-old female patient with a previous history of pelvic pain and dysmenorrhea, whose ultrasound showed an enlarged and heterogeneous uterus. Complete hysterectomy was performed, and the anatomopathological examination showed leiomyomas without evidence of malignancy. One month later, the patient manifested dyspnea and chest pain. A neoplastic thrombus was identified, extending from the inferior vena cava to the right atrium, for which we proceeded with cavo-atrial thrombectomy under Normothermic Cardiopulmonary Bypass (CPB) with Warm Blood Cardioplegia (WBC). A metastatic lung injury of non-malignant histology was also detected. Discussion: Uterine leiomyoma is a very common benign tumor of the female genital tract. IVL with ICLM are rare and difficult-to-treat complications, whose etiology is a direct vascular invasion by a primary uterine leiomyoma, although it is still controversial. The incidence of ICLM is 10 to 30% of IVL cases. The main symptoms of ICLM are dyspnea, syncope, edema of the lower extremities and palpitations. Treatment is based on complete surgical removal of the tumor thrombus. Studies demonstrated that the one-stage procedure is safer from the patient's perspective and that CPB with WBC reduced intraoperative blood loss and total operative time, ensuring a less traumatic postoperative. Conclusions: Most patients with uterine leiomyoma are asymptomatic and acute complications are rare. In ICLM clinical manifestations are related to heart failure and flow obstruction. Because of the severity of the condition and the curative potential of treatment, surgery is morbid but highly recommended. The use of CPB with WBC improved the postoperative period and increased the patient's quality of life.